The association between transition into grandparenthood and Chinese older adults’ subjective well-being and health: a longitudinal study - Wang, Huan; Wang, Danyang; Yu, Jiahao; Wang, Jin (Frontiers in Public Health, 2025)
BackgroundDue to low birth rates, longer life expectancy, and later childbearing, an increasing number of individuals become grandparents later in life. The transition into grandparenthood—encompassing role acquisition, duration, and role engagement—is crucial for understanding the well-being and health of older adults. However, the connection between this transition and well-being and health outcomes among older adults remains underexplored, particularly in a Chinese context that emphasizes family lineage. This study addresses this gap by analyzing longitudinal data to examine how grandparenthood transitions relate to subjective well-being and health among Chinese older adults.MethodsUsing longitudinal data from the China Longitudinal Aging Social Survey (CLASS) 2014–2020, this study investigates the associations between grandparenthood transition —specifically, grandparent role acquisition (i.e., becoming a grandparent), role duration (i.e., duration of being a grandparent), and role enactment (i.e., providing grandchild care)—and three well-being outcomes: life satisfaction, depressive symptoms, and self-rated health. Fixed-effects models are employed to account for unobservable time-invariant heterogeneity.ResultsThe transition into grandparenthood is associated with lower life satisfaction, increased depressive symptoms, and improved self-rated health among older adults in China, though these effects appear to be short-term. Additionally, the well-being and health benefits of becoming a grandparent are more pronounced for men compared to their female counterparts.ConclusionThe findings indicate that transitioning into the role of a grandparent, rather than caregiving per se, is negatively associated with certain aspects of well-being for older adults in the short term. However, this transition seems more beneficial for older men. These results underscore the relationship between becoming a grandparent and changes in the daily lives and well-being of older adults, suggesting that policymakers should develop targeted family support systems to help facilitate a positive adjustment during this transition, especially for grandmothers.